PREDATION OF Euseius emanus (El Banhawy, 1979) ON Oligonychus beeri Estebanes & Baker, 1968 - Tomas de la Cruz, Lelia de; Vergara Cobian, Clorinda; Rodriguez Berrio, Alexander; Huanca Maldonado, Javier; Giraldo Mendoza, Alfredo; Carlos Lofego, Antonio [UNESP] (Univ Nacional Agraria La Molina, 2021)
The predation capacity of protonymphs and adults of E. emanus on eggs, larvae, protonymphs and adults of O. beeri was evaluated under controlled conditions of temperature and humidity. According to the tests, the adult females had a higher predation capacity (mean = 23.18 larvae) than the protonymphs (mean = 11.15 larvae) and the adult males (mean = 8.05 larvae). Both stages of development of E. emanus consumed higher amounts of larvae and protonymphs, while their consumption of eggs was minimal.
Keywords: biological control; predatory capacity; Euseius emanus; Oligonychus beeri